Outcome of Vessel Sealing System Tonsillectomy vs Electrocautery Tonsillectomy, Kalasin Hospital - Chukchuen, Patchareeya (Srinagarind Medical Journal, 2024)
Background and Objective: Tonsillectomy is performed due to recurring infections and inflammation. The upper respiratory tract obstruction and tonsil cancer may be present due to the size of the tonsils. There are many different surgical procedures, but problems still occur. The outcomes of vessel sealing system tonsillectomy and electrocautery tonsillectomy in this study are compared about operative time, intraoperative blood loss, postoperative bleeding, length of hospital stay and medical expense. Methods: Retrospective descriptive analysis of 95 individuals who were done tonsillectomy from 1 January 2020 to 31 May 2023. Results: The mean values of vessel sealing system tonsillectomy and electrocautery tonsillectomy are contrasted. The mean operative time 24.34±6.49 and 30.59±10.28 minutes. Intraoperative blood loss 5.97±4.11 and 9.71±5.50 cc. Length of hospital stay 3.48±0.67 and 3.41±0.56 days. Medical expense 17,556.90±2,854.60 and 13,249.02±2,800.40 Bahts, respectively. Statistically significant shows that the surgical method is related to the operative time, intraoperative blood loss and medical expense. (p< 0.05). Conclusion: As the results, there are less operative time and intraoperative blood loss after vessel sealing system tonsillectomy. When comparing the two surgical procedures, nearby results of tonsillectomy were obtained. Selecting treatment options and choosing between surgical treatment is what makes tonsillectomy safe and beneficial for patients.